2014
DOI: 10.1177/1479164114547704
|View full text |Cite
|
Sign up to set email alerts
|

The role of lectin-like oxidised low-density lipoprotein receptor-1 in vascular pathology

Abstract: The lectin-like oxidised low-density lipoprotein receptor-1 (LOX-1) is a vascular scavenger receptor that plays a central role in the pathogenesis of atherothrombotic disease, which remains the main cause of mortality in the Western population. Recent evidence indicates that targeting LOX-1 represents a credible strategy for the management vascular disease and the current review explores the role of this molecule in the diagnosis and treatment of atherosclerosis. LOX-1-mediated pro-atherogenic effects can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(80 reference statements)
0
8
0
1
Order By: Relevance
“…LOX-1, the main endothelial receptor of oxLDL, is responsible for the degradation of oxLDL. The binding of oxLDL to LOX-1 can activate NF-κB and then induce the expression of ICAM-1, VCAM-l, TNF-α, and IL-6, as well as MCP-l and MMP-9 levels [16,32,33]. We observed that catalpol decreased oxLDL levels in both serum and hepatic tissue and LOX-1 expression in the aorta.…”
mentioning
confidence: 58%
“…LOX-1, the main endothelial receptor of oxLDL, is responsible for the degradation of oxLDL. The binding of oxLDL to LOX-1 can activate NF-κB and then induce the expression of ICAM-1, VCAM-l, TNF-α, and IL-6, as well as MCP-l and MMP-9 levels [16,32,33]. We observed that catalpol decreased oxLDL levels in both serum and hepatic tissue and LOX-1 expression in the aorta.…”
mentioning
confidence: 58%
“…Under acute inflammatory conditions, the lectin-like extracellular domain of LOX-1 may be released from the cell membrane into circulation as the soluble LOX-1 (sLOX-1) protein (28,29). Therefore, sLOX-1 may be considered a potential diagnostic and prognostic marker for atherosclerosis-associated events, including acute coronary syndrome (28,29). LOX-1 is the major receptor for ox-LDL uptake by ECs and induces a series of pathological processes in ECs (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expression on endothelial cells, LOX-1 is also expressed on other cells, such as VSMCs, fibroblasts, myocardial cells, and macrophages. LOX-1 mediated signaling has been implicated in the development and progression of cardiovascular diseases 14, 27) . By interacting with ox-LOX-1, LOX-1 acts as a key regulator in activating endothelial cells, promoting the adhesion ability of monocytes to the endothelium, and altering VSMCs phenotype by increasing the levels of inflammatory chemokines and adhesion molecules, including monocyte chemotactic protein 1 (MCP-1), E-selectin, P-selectin, and vascular cell adhesion molecule-1 (VCAM-1) 2830) .…”
Section: Discussionmentioning
confidence: 99%